Asymmetric Effects of Fashions on the Formation and Dissolution of Networks: Board Interlocks with Internet Companies, 1996–2006 - Yue, Lori Qingyuan (Organization Science, 2012)
This paper extends the contextual perspective of network evolution to account for a more complete process of network evolution by showing that the impacts of fads and fashions on the formation and dissolution of interorganizational networks are asymmetric. Building on contact theory, this paper proposes that direct contact affords a flow of knowledge that counters tendencies to social conformity. Network dissolution differs from network formation in that partners have already obtained direct information. As a result, network dissolution is not as responsive to fads and fashions as network formation, and network structures induced by fads and fashions often survive beyond the life cycle of a fashion. An analysis of the interlocking ties of S&P 1500 firms with Internet companies from 1996 to 2006 supports the view that fads and fashions have asymmetric effects on the evolution of networks and also shows that (1) fads and fashions have a strong impact on the formation of networks but not on their dissolution, (2) the networking behaviors of organizations with direct contact are less induced by fads and fashions, and (3) the networks formed by organizations with direct contact during the heyday of a fashion survive longer.